Read-SpaM: assembly-free and alignment-free comparison of bacterial genomes with low sequencing coverage - Anna-Katharina Lau; Svenja Dörrer; Chris-André Leimeister; Christoph Bleidorn; Burkhard Morgenstern (BMC Bioinformatics, 2019)
Abstract Background In many fields of biomedical research, it is important to estimate phylogenetic distances between taxa based on low-coverage sequencing reads. Major applications are, for example, phylogeny reconstruction, species identification from small sequencing samples, or bacterial strain typing in medical diagnostics. Results We adapted our previously developed software program Filtered Spaced-Word Matches (FSWM) for alignment-free phylogeny reconstruction to take unassembled reads as input; we call this implementation Read-SpaM. Conclusions Test runs on simulated reads from semi-artificial and real-world bacterial genomes show that our approach can estimate phylogenetic distances with high accuracy, even for large evolutionary distances and for very low sequencing coverage.